Peningkatan Protein Black Soldier Fly (BSF) Untuk Pakan Ternak Sebagai Hasil Biokonversi Sampah Makanan - Aurelia Anggita Putri; Mohamad Mirwan (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Based on the data obtained, 1.3 billion tons of food waste are generated annually worldwide. This amount constitutes one-third of the food successfully produced for human consumption. And Indonesia has succeeded in becoming the second largest producer of food waste in the world. In this study, observations will be made of the effect of the mixture composition on food waste originating from Jambangan TPS on BSF larvae bioconversion. The research was conducted on a field scale with a running time of 12 days. Data analysis carried out included waste reduction index, efficiency conversion of digestive feed, biomass weight gain, compost yield testing and protein content in larvae. Compost results will be compared with SNI 19-7030-2004 concerning Compost Specifications from Domestic Organic Waste. And the results of the protein content in the larvae will be compared with SNI (8290.1: 2016) concerning laying hen feed (production period) and with conventional chicken feed. The results showed that the highest percentage of reduction ability was from the food waste and amino acid reactor which managed to reach 80%, and the final weight of the larvae touched 0.2-0.3 gr. The laboratory test results stated that the compost and protein content complied with the existing SNI. Meanwhile, the palatability test states that fresh maggot has the best value. But the drawback of fresh maggot is that it can cause damage to the digestive tract, besides that it also has low shelf life..